2018
DOI: 10.1159/000486853
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Early Pregnancy Risk Prediction Model for Gestational Diabetes Mellitus

Abstract: Introduction: Accurate early risk prediction for gestational diabetes mellitus (GDM) would target intervention and prevention in women at the highest risk. We evaluated novel biomarker predictors to develop a first-trimester risk prediction model in a large multiethnic cohort. Methods: Maternal clinical, aneuploidy and pre-eclampsia screening markers (PAPP-A, free hCGβ, mean arterial pressure, uterine artery pulsatility index) were measured prospectively at 11–13+6 weeks’ gestation in 980 women (248… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 34 publications
4
87
0
1
Order By: Relevance
“…PAPP-A2 might also be able to predict GD development in late pregnancy, although any such association would need to be further investigated in prospective studies. The increased risk of adverse outcomes associated with GD coupled with the frequently late diagnosis of the conditions has given rise to numerous studies focused on identifying early-pregnancy biomarkers for GD [22,24,28,29]. PAPP-A2 levels in early pregnancy may also merit investigation as a potential pre-screening biomarker to identify low-risk women who can be spared from performing the OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…PAPP-A2 might also be able to predict GD development in late pregnancy, although any such association would need to be further investigated in prospective studies. The increased risk of adverse outcomes associated with GD coupled with the frequently late diagnosis of the conditions has given rise to numerous studies focused on identifying early-pregnancy biomarkers for GD [22,24,28,29]. PAPP-A2 levels in early pregnancy may also merit investigation as a potential pre-screening biomarker to identify low-risk women who can be spared from performing the OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…Further, prospective studies showed that the TG level was an independent risk factor for developing diabetes in middle-aged women [11,12]. In a prospective case-control study, higher TG levels were observed at 11-14 weeks of gestation in women with GDM, and multivariate regression analysis indicated that TG levels were a significant predictor of a subsequent diagnosis of GDM [13]. However, fewer studies have characterized the relationship between TG levels during pregnancy and the risk of postpartum AGM in GDM patients.…”
Section: Introductionmentioning
confidence: 95%
“…Adiponectin is another glycoprotein that has been associated with GDM [22]. Adiponectin is a protein hormone that has a role in regulating glucose levels and fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%